PERILAKU CARING PERAWAT PADA PASIEN PASCA CRANIOTOMY DI RUANG ICU RSD GUNUNG JATI KOTA CIREBON - Ahmad Syaripudin (LPPM ITEKES Mahardika, 2018)
Background: Craniotomy is an operation to open the skull (cranium) in a purpose to repair brain damage. Post craniotomy patients require a rigorous general monitoring of the condition until optimum awareness. The recovery for post-craniotomy patients on ICU room is about 2 days. In order to stimulate the patients awareness, caring behavior is very needed especially in ICU room. Purpose: The purpose of this research was to determine of nursing caring behavior in post craniotomy patient in ICU room Gunung Jati Public Hospital in Cirebon. Method: A descriptive correlation with cross sectional approach was attempted in this research. A total sampling was used as the technique of sampling. The data of 30 respondents pasca craniotomy were analyzed statistically by using chi square test. The collecting data used the caring questionnaire. This research on May-June 2017. Result: The results showed that 15 out of 15 (50.0%) caring and 15 (50.0%) not caring. The nurse in ICU room can applied caring behavior in post craniotomy patient to support the recovery of the patient level of awareness